Electromagnetic imaging of magma across the Narmada Son lineament, central India - Rao, C. K.; Ogawa, Y.; Gokarn, S. G.; Gupta, Gautam (My University, 2004)
Wide band magnetotelluric (MT) studies were undertaken over a 130 km long, approximately north-south profile in central India across the Narmada Son lineament (NSL) that runs through Indian peninsula in ENE-WSW direction and its contiguous region. The NSL and its contiguous zone in the study region consists of Narmada graben, Satpura horst and Tapti-Purna graben, which are arranged from north to south as this order within the zone. The obtained deep crustal resistivity structure shows two deep-seated conductive features, which locate below the Tapti River on the southern flank of the Satpura horst (South conductor) and below Dorwa on the Narmada graben (North conductor), respectively. Both conductive features have identical resistivities of 10–200 Ohm-m and extend from 7 km to about 50 km in depth. Integration with gravity, heat flow and the deep seismic reflection studies suggests that these conductive bodies may have different causative factors. The South conductor, which is embedded in a high heat flow and a negative Bouguer gravity anomaly area, seems to be due to magma intrusion into the crust leading to high heat flows in the region. On the contrary, the North conductor is not characterized by high heat flow however seismic reflectors in this region show a domal feature. It is thus conjectured that the north conductive feature may be caused by the tectonic activity and partially molten magma emplacement from the asthenospheric levels into the crust.
Keywords: Magnetotellurics; Resistivity; Conductor lineament; Magma; India; Electromagnetic; Narmada Son lineament (NSL)